Applying Bella H. Banathy’s Instructional Design to Islamic Education (Fiqh) in the Context of the Digital Era - Putri Rahmawati; Iftitah Ardiwira Pramesti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Applying Bella H. Banathy’s Instructional Design to Islamic Education (Fiqh) in the Context of the Digital EraObjective: This study aims to apply Bella H. Banathy's Instructional Design in teaching Islamic Education subjects at GIKI 2 Surabaya Senior High School. Method: This research employed a qualitative approach. Data were collected using triangulation techniques (a combination of methods), and analysis was conducted inductively. The study was conducted in 2023 with second-grade students at GIKI 2 Surabaya as the research subjects, selected through purposive sampling. Results: The application of Bella H. Banathy's instructional design model was influenced by several factors, including goal-setting, assessment, learning activities, media usage, and time allocation, all of which contributed to achieving learning objectives. Conclusion: Bella H. Banathy's Instructional Design allows teachers to create engaging learning experiences that motivate and actively involve students in the learning process of Islamic Religious Education, particularly in Fiqh material. Contribution: This research offers policy recommendations for schools and educational institutions to integrate instructional design with technology into the Islamic Education curriculum, ultimately enhancing the quality of religious education across educational levels.INDONESIAN: Penerapan Desain Instruksional Bella H. Banathy pada Mata Pelajaran Pendidikan Agama Islam di Era DigitalTujuan: Penelitian ini bertujuan untuk menerapkan Desain Instruksional Bella H. Banathy dalam pengajaran Mata Pelajaran Pendidikan Agama Islam di SMA Giki 2 Surabaya. Metode: Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan data menggunakan teknik triangulasi (gabungan). Analisis data dilakukan secara induktif atau kualitatif. Penelitian ini dilakukan pada tahun 2023. Subjek penelitian ini adalah siswa kelas dua SMA GIKI 2 Surabaya. Subjek penelitian ini dipilih dengan menggunakan teknik purposive sampling. Hasil: Penerapan model desain pembelajaran Bella H Banathy dipengaruhi oleh penyusunan tujuan, penilaian, kegiatan, media dan waktu agar tujuan dapat tercapai. Kesimpulan: Dengan menggunakan Desain Instruksional Bella H. Banathy, guru dapat merancang materi pembelajaran yang menarik, dan memotivasi serta melibatkan siswa secara aktif dalam proses pembelajaran Pendidikan Agama Islam (meteri Fiqih). Kontribusi: Penelitian ini berkontribusi sebagai rekomendasi kebijakan bagi pihak sekolah dan lembaga pendidikan untuk mengintegrasikan teknologi dengan desain instruksional dalam kurikulum PAI, yang dapat meningkatkan kualitas pendidikan agama di seluruh tingkat pendidikan.